2017
DOI: 10.1002/jwmg.21312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of industrial and investigator disturbance on Arctic‐nesting geese

Abstract: Oil and gas development on the Arctic Coastal Plain (ACP) of Alaska, USA may have effects on Arctic‐nesting birds. To estimate effects of industrial activity and investigator disturbance on avian productivity, we monitored nests of greater white‐fronted geese (Anser albifrons) with digital cameras and periodic nest visits during 2013–2014 at 2 sites on the ACP. A disturbed site was adjacent to human‐made infrastructure and industrial clean‐up activities initiated at the onset of the study and a control site wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 46 publications
1
38
0
Order By: Relevance
“…comm.) and in a study area ~80 km to the northeast (Meixell and Flint 2017). The low nest survival in 2013 suggests that predators can impact Pacific and yellow-billed loons in years with low mictrotine abundance.…”
Section: Nest Site Selection and Predation Riskmentioning
confidence: 89%
See 1 more Smart Citation
“…comm.) and in a study area ~80 km to the northeast (Meixell and Flint 2017). The low nest survival in 2013 suggests that predators can impact Pacific and yellow-billed loons in years with low mictrotine abundance.…”
Section: Nest Site Selection and Predation Riskmentioning
confidence: 89%
“…Nest predation is one of the major causes of nest failure among tundra breeding birds (Liebezeit et al 2011, Meixell andFlint 2017), and nest site selection may be an adaptive response to predators in some species (Forstmeier and Weiss 2004). Our results suggest that Pacific and yellow-billed loons choose nest sites based on nest predation risk (Petersen Shore 50 55 8 113 Vegetation mat 50 8 13 71 Island 133 47 12 192 Peninsula 17 21 0 38 Channel 0 12 0 12 Total 250 143 33 426 1979, Haynes et al 2014b).…”
Section: Nest Site Selection and Predation Riskmentioning
confidence: 99%
“…Finally, we note that nest searching effort and frequency of nest visits likely increased in recent years as researchers learned how best to obtain accurate estimates of nest survival (11)(12)(13). Researchers also intensified their activities (e.g., capturing adults to band, tag, and collect samples and placing monitoring equipment near nests, which may increase the predation rate) (14,15). Thus, an increase in the quality of data reporting as well as increased research activity around nests may have further induced a time-on July 5, 2020 http://science.sciencemag.org/ Downloaded from dependent bias in estimates with an underestimation of true predation rates in the historic data (see above), and perhaps an overestimation in the contemporary data.…”
mentioning
confidence: 99%
“…Results for observer effects are consistent with findings from other studies on the central Arctic Coastal Plain involving king eiders (Somateria spectabilis; Bentzen and others, 2008) and loons (Uher-Koch and others, 2015). Meixell and Flint (2017) conclude that these results demonstrate a differential response by nesting geese to varying types of disturbance. Whereas observer visits were associated with direct human encroachment at nests that caused female geese to be absent from nests longer, sources of industrial disturbance in their study were characterized primarily by vehicular, aircraft, and foot travel that followed similar routes and usually did not directly approach nest sites.…”
Section: Disturbance To Birds From Industry and Investigatorsmentioning
confidence: 52%
“…Although predation events were determined to be the primary cause of nest failure, the authors found that predator abundance was not related to nest survival and non-subsidized predators accounted for 32-77 percent of the total predators observed during surveys. Meixell and Flint (2017) also examined predators and distance to industrial disturbance in relation to nesting behavior and success of greater white-fronted geese (Anser albifrons). Additionally, these authors quantified the effect of observer visits to nests.…”
Section: Disturbance To Birds From Industry and Investigatorsmentioning
confidence: 99%